Nickel-manganese-based sodium ion battery positive electrode material as well as preparation method and application thereof

By using nickel-manganese-based P2-type layered oxide material in the sodium ion battery positive electrode material, the problem of structural distortion and poor circulation performance of the sodium ion battery positive electrode material is solved through the specific element replacement strategy, and high specific capacity and excellent circulation are achieved Stable performance positive electrode material.

CN119400852AActive Publication Date: 2025-02-07SHANGHAI JIAOTONG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411535142.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The positive electrode material of sodium ion battery is prone to structural distortion at high voltages, affecting the battery circulation performance, and existing electrode materials are difficult to directly apply to sodium ion batteries.

Method used

Using nickel-manganese-based P2-type layered oxide material, the chemical formula is formed by substitution strategies of specific elements, such as zinc, lithium, copper ions to replace part of nickel ions, and titanium or tin ions to replace part of manganese ions, forming the chemical formula Na0.67Ni0.25- The cathode material of xM1xMn0.75-yM2yO2 was prepared by high temperature sintering.

Benefits of technology

The high specific capacity and excellent cycling stability of the cathode material are achieved. The initial discharge capacity is about 90-100mAh/g at a 1C current density, and the capacity retention rate after cycling is above 80%, while the preparation cost and energy consumption are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400852A_ABST
    Figure CN119400852A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion positive electrode materials, and particularly discloses a nickel-manganese-based sodium ion battery positive electrode material as well as a preparation method and application thereof. The positive electrode material is a P2-type layered oxide material, the chemical general formula of the P2-type layered oxide material is Na < 0.67 > Ni < 0.25-x > M < 1x > Mn < 0.75-y > M < 2y > O < 2 >, M < 1 > is one or more of Zn, Li or Cu, M < 2 > is one or more of Ti or Sn, and 0.05 lt; x is less than or equal to 0.2, 0.05 lt; and y < = 0.2. The invention also discloses a preparation method of the material and an application of the material in a battery material. Through a specific element substitution strategy, different metal ions are substituted on transition metal sites, so that the material has relatively high specific capacity and shows excellent cycle stability, the initial discharge capacity under 1C current density is about 90-100mAh / g, and the capacity retention ratio after circulation is more than 80%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion positive electrode materials, and in particular relates to a nickel-manganese-based sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] The new generation of electrochemical energy storage technology can effectively alleviate the problem of non-renewable energy consumption, such as the application of lithium-ion batteries. However, in recent years, due to the price fluctuations of lithium carbonate and the increasing demand for lithium in electronic devices, people have begun to shift their attention to sodium-ion batteries, and the research on sodium-ion batteries has gradually ushered in new opportunities. Sodium and lithium are in the same main group, but sodium ions are The radius is much larger than that of lithium ions In the process of deintercalation of the bulk structure, more serious structural distortion will inevitably occur, which will eventually affect the battery cycle performance. In addition, due to the larger radius, the sodium atoms in the transition metal layer usually have octahedral coordination, while lithium has both octahedral and tetrahedral forms, which makes it difficult for some electrode materials suitable for lithium-ion batteries to be directly used in sodium-ion batteries. The development of sodium-ion battery electrode materials requires further research.

[0003] Among the various components of sodium-ion batteries, the positive electrode material determines the energy density of the entire battery system. Layered oxides are usually composed of electrochemically active elements, have low cost, and show excellent application prospects. Among them, the structure of the P2-type positive electrode material is relatively stable, and the sodium ion migration speed is relatively fast. Usually when the voltage exceeds 4.2V, the material will undergo a significant phase change, triggering changes in the system structure, and the phase change becomes more significant when it reaches 4.3V. Element substitution is an effective strategy to inhibit adverse phase change behavior, but it reduces the specific capacity of the material to a certain extent. Therefore, the development of a positive electrode material with excellent cycle performance and high specific capacity is of great significance for the application of sodium-ion batteries. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a nickel-manganese-based sodium-ion battery positive electrode material. Through a specific element substitution strategy, different metal ions are replaced at the transition metal site, so that the material has a higher specific capacity and exhibits excellent cycle stability. The initial discharge capacity at 1C current density is about 90-100mAh / g, and the capacity retention rate after cycling is above 80%.

[0005] The technical solution of the present invention is as follows:

[0006] The present invention relates to a nickel-manganese-based sodium ion battery positive electrode material, wherein the positive electrode material is a P2-type layered oxide material, and its general chemical formula is Na 0.67 Ni 0.25-x M1 x Mn 0.75-yM2 y O2, wherein M1 is one or more of Zn, Li or Cu, M2 is one or more of Ti or Sn, 0.05 < x ≤ 0.2, 0.05 < y ≤ 0.2, and zinc ions, lithium ions or copper ions replace part of nickel ions, and titanium ions or tin ions replace part of manganese ions.

[0007] The present invention also discloses a preparation method of the above-mentioned positive electrode material, comprising the following steps:

[0008] (1) According to the stoichiometric ratio of the chemical general formula, take a sodium salt that is 1 - 1.05 times the stoichiometry of the required sodium element and mix it with the remaining metal salts of the required stoichiometry;

[0009] (2) After drying, sinter at 500 - 800 °C for 6 - 18 h, and cool to room temperature to obtain the positive electrode material.

[0010] In an embodiment of the present invention, the sodium salt in step (1) is a carbonate or acetate, and the remaining metal salts are one or two of oxides, oxalates, carbonates or acetates.

[0011] In an embodiment of the present invention, step (2) includes placing the dried metal salts in a muffle furnace and heating to the set temperature for sintering at a rate of 3 - 5 °C / min.

[0012] In an embodiment of the present invention, before preparing the positive electrode material, it also includes verifying its feasibility: taking sodium salt, nickel salt and manganese salt according to the stoichiometry shown by the chemical formula Na 0.67 Ni 0.25 Mn 0.75 O2, mixing them evenly, collecting the powder and drying it after mixing, transferring it to a muffle furnace, and sintering at 500 - 800 °C for 6 - 18 h to obtain Na 0.67 Ni 0.25 Mn 0.75 O2 material.

[0013] In an embodiment of the present invention, it also includes placing the cooled positive electrode material in a mortar and grinding it into powder, then transferring it to a centrifuge tube for sealing and storing it in an argon glove box for later use.

[0014] The present invention also discloses a positive electrode sheet for a sodium ion battery, and the positive electrode sheet includes the above-mentioned positive electrode material.

[0015] The present invention also discloses a sodium ion secondary battery including the above-mentioned positive electrode sheet.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0017] A nickel-manganese-based sodium ion battery positive electrode material of the present invention is obtained by a specific element substitution strategy to obtain a positive electrode material suitable for sodium ion batteries. The positive electrode material shows excellent performance in a half-cell, with an initial discharge capacity of about 90-100mAh / g at a current density of 1C, and a capacity retention rate after cycling of more than 80%. At the same time, the raw materials used are cheap and available, showing great advantages in the large-scale preparation of positive electrode materials; and it is environmentally friendly and will not pollute the environment, which is in line with the concept of green energy. Compared with the liquid phase method, the present invention adopts a full solid phase method, which has the characteristics of simple operation and reduces the preparation process to a certain extent. Generally speaking, P2-type layered oxide materials are usually prepared at a temperature above 900°C. The maximum temperature for preparing the positive electrode material of the present invention is only 800°C, which also saves energy consumption to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A nickel-manganese-based sodium ion battery positive electrode material Na 0.67 Ni 0.25 Mn 0.75 Half-cell charge and discharge performance diagram of O2 at 0.2C current density;

[0019] Figure 2 A nickel-manganese-based sodium ion battery positive electrode material Na of Example 2 of the present invention 0.67 Ni 0.15 Cu 0.1 Mn 0.65 Ti 0.1 Half-cell cycle performance diagram of O2 at 1C current density;

[0020] Figure 3 A nickel-manganese-based sodium ion battery positive electrode material Na of Example 4 of the present invention 0.67 Ni 0.15 Li 0.1 Mn 0.55 Ti 0.2 Half-cell cycle performance diagram of O2 at 1C current density;

[0021] Figure 4 A nickel-manganese-based sodium ion battery positive electrode material Na of Example 5 of the present invention 0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 SEM image of O2;

[0022] Figure 5 A nickel-manganese-based sodium ion battery positive electrode material Na of Example 5 of the present invention 0.67 Ni 0.2 Zn 0.05 Mn 0.55Ti 0.2 XRD pattern of O2;

[0023] Figure 6 A nickel-manganese-based sodium-ion battery cathode material Na for Example 5 of the present invention 0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 Half-cell rate performance graph of O2;

[0024] Figure 7 A nickel-manganese-based sodium-ion battery cathode material Na for Example 5 of the present invention 0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 Half-cell cycle performance graph of O2 at 1C current density;

[0025] Figure 8 A nickel-manganese-based sodium-ion battery cathode material Na for Example 5 of the present invention 0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 Full-cell cycle performance graph of O2 at 0.5C current density. Detailed implementation manners

[0026] To make the above objects, features and advantages of the present invention more obvious and understandable, the following detailed description of the specific implementation manners of the present invention will be given with reference to the accompanying drawings.

[0027] Many specific details are set forth in the following description in order to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the connotation of the present invention. Therefore, the present invention is not limited by the specific implementations disclosed below.

[0028] A nickel-manganese-based sodium-ion battery cathode material in an embodiment of the present invention, wherein the cathode material is a P2-type layered oxide material, and its chemical general formula is Na 0.67 Ni 0.25-x M1 x Mn 0.75-y M2 y O2, wherein M1 is one or more of Zn, Li or Cu, M2 is one or more of Ti or Sn, 0.05 < x ≤ 0.2, 0.05 < y ≤ 0.2, zinc ions, lithium ions or copper ions replace part of the nickel ions, and titanium ions or tin ions replace part of the manganese ions. Its preparation method includes the following steps:

[0029] (1) according to the stoichiometric ratio of the above chemical formula, a sodium salt in an amount of 1-1.05 times the stoichiometric amount of the required sodium element is mixed with the remaining metal salts in the required amounts; the sodium salt is a carbonate or an acetate, and the remaining metal salts are one or two of oxides, oxalates, carbonates or acetates;

[0030] (2) After drying, the metal salt is placed in a muffle furnace, heated to 500-800° C. at a rate of 3-5° C. / min, and sintered at high temperature for 6-18 hours, and then cooled to room temperature to obtain the positive electrode material.

[0031] (3) The cooled positive electrode material is placed in a mortar and ground into powder, then transferred to a centrifuge tube, sealed, and stored in an argon glove box for later use.

[0032] Before preparing the positive electrode material, the feasibility of the positive electrode material is verified to see whether it can be used as a positive electrode material for a sodium ion battery. The positive electrode material must at least have a high specific capacity, including: 0.67 Ni 0.25 Mn 0.75 The stoichiometric amount shown in O2 is taken, sodium carbonate, nickel acetate and manganese carbonate are mixed, the powder is collected and dried, transferred to a muffle furnace, and sintered at 500-800℃ for 6-18h to obtain Na 0.67 Ni 0.25 Mn 0.75 O2 material.

[0033] To verify Na 0.67 Ni 0.25 Mn 0.75 Electrochemical properties of O2. Take 2032 button cells as an example and assemble them in an argon glove box. Before assembling the battery, it is necessary to prepare the positive electrode sheet, negative electrode sheet and separator, etc. The preparation process of the positive electrode sheet is to obtain Na 0.67 Ni 0.25 Mn 0.75 80mg of O2 material, 10mg of conductive carbon black and 10mg of binder PVDF were uniformly mixed in a mortar, and then NMP was added and scraped on the surface of the aluminum foil. After being stored in a vacuum drying oven for a period of time, it was cut into 12mm pole pieces as the positive electrode and assembled with the sodium sheet as the negative electrode into a half-cell. After standing for a few hours, it was connected to the Xinwei test system for constant current charge and discharge test, and the test voltage range was 2-4.3V. Figure 1 As shown in the figure, at a current density of 0.2C, its initial capacity is as high as 152.6mAh / g. Due to the instability of the crystal structure, the capacity decays rapidly during the subsequent cycles.

[0034] Example 1

[0035] A nickel-manganese-based sodium ion battery positive electrode material Na in Example 1 of the present invention0.67 Ni 0.2 Zn 0.05 Mn 0.65 Ti 0.1 O2, which comprises the following preparation steps:

[0036] (1) Zn / Ti co-substituted Na 0.67 Ni 0.25-x Zn x Mn 0.75-y Ti y O2 electrode material, where x = 0.05, y = 0.1; with a total mass of about 2g, according to Na 0.67 Ni 0.2 Zn 0.05 Mn 0.65 Ti 0.1 The stoichiometric amount shown in O2 is to mix sodium carbonate, nickel acetate, zinc acetate, manganese carbonate and titanium dioxide, and after mixing evenly, collect the powder and dry it;

[0037] (2) After drying, the powder is placed in a round alumina crucible and sintered in a muffle furnace at a high temperature, the temperature is raised to 700°C at a rate of 3°C / min and maintained for 6 hours, and then cooled to room temperature to obtain the positive electrode material Na 0.67 Ni 0.2 Zn 0.05 Mn 0.65 Ti 0.1 O2;

[0038] (4) The cooled positive electrode material is placed in a mortar and ground for a period of time. After it is completely powdered, it is sealed in an ordinary centrifuge tube and stored in an argon glove box for later use.

[0039] The method for assembling the 2032 type button cell is the same as above, which can exhibit a discharge specific capacity of 90 mAh / g at a current density of 1 C and achieve an efficiency of 80% after 30 stable cycles.

[0040] Example 2

[0041] A nickel-manganese-based sodium ion battery positive electrode material Na in Example 2 of the present invention 0.67 Ni 0.15 Cu 0.1 Mn 0.65 Ti 0.1 O2, which comprises the following preparation steps:

[0042] (1) Copper / Titanium co-substituted Na 0.67 Ni 0.25-x Cu x Mn 0.75-y Ti y O2 electrode material, where x = 0.1, y = 0.1; with a total mass of about 2g, according to Na0.67 Ni 0.15 Cu 0.1 Mn 0.65 Ti 0.1 The stoichiometric amount shown in O2 is to mix sodium carbonate, nickel acetate, copper acetate, manganese carbonate and titanium dioxide, and after mixing evenly, collect the powder and dry it;

[0043] (2) After drying, the powder is placed in a round alumina crucible and sintered in a muffle furnace at a high temperature, the temperature is raised to 800°C at a rate of 3°C / min and maintained for 12 hours, and then cooled to room temperature to obtain the positive electrode material Na 0.67 Ni 0.15 Cu 0.1 Mn 0.65 Ti 0.1 O2;

[0044] (3) The cooled positive electrode material is placed in a mortar and ground for a period of time. After it is completely powdered, it is sealed in an ordinary centrifuge tube and stored in an argon glove box for later use.

[0045] The method of assembling 2032 button cells is the same as above, and the cycle performance at 1C current density is measured as follows: Figure 2 As shown, it exhibits a discharge specific capacity of 94.7 mAh / g. After 50 cycles, a discharge specific capacity of 88.1 mAh / g is obtained, and the capacity retention rate is 93.0%.

[0046] Example 3

[0047] A nickel-manganese-based sodium ion battery positive electrode material Na in Example 3 of the present invention 0.67 Ni 0.15 Cu 0.1 Mn 0.6 Sn 0.15 O2, which comprises the following preparation steps:

[0048] (1) Copper / Sn co-substituted Na 0.67 Ni 0.25-x Cu x Mn 0.75-y Sn y O2 electrode material, where x = 0.1, y = 0.15; with a total mass of about 2g, according to Na 0.67 Ni 0.15 Cu 0.1 Mn 0.6 Sn 0.15 The stoichiometric amount shown in O2 is to mix sodium carbonate, nickel acetate, copper acetate, manganese carbonate and tin oxalate, and after mixing evenly, collect the powder and dry it;

[0049] (2) After drying, the powder is placed in a round alumina crucible and sintered in a muffle furnace at a high temperature, the temperature is raised to 800°C at 3°C / min and maintained for 8 hours, and then cooled to room temperature to obtain the positive electrode material Na 0.67 Ni 0.15 Cu 0.1 Mn 0.6 Sn 0.15 O2;

[0050] (3) The cooled positive electrode material is placed in a mortar and ground for a period of time. After it is completely powdered, it is sealed in an ordinary centrifuge tube and stored in an argon glove box for later use.

[0051] The method for assembling the 2032 type button cell is the same as above, which can exhibit a discharge specific capacity of 95 mAh / g at a current density of 1 C and achieve an efficiency of 80% after 60 stable cycles.

[0052] Example 4

[0053] A nickel-manganese-based sodium ion battery positive electrode material Na in Example 4 of the present invention 0.67 Ni 0.15 Li 0.1 Mn 0.55 Ti 0.2 O2, which comprises the following preparation steps:

[0054] (1) Lithium / Titanium co-substituted Na 0.67 Ni 0.25-x Li x Mn 0.75-y Ti y O2 electrode material, where x = 0.1, y = 0.2; with a total mass of about 2g, according to Na 0.67 Ni 0.1 Li 0.1 Mn 0.6 Ti 0.2 The stoichiometric amount shown in O2 is to mix sodium carbonate, nickel acetate, lithium acetate, manganese carbonate and titanium dioxide, and after mixing evenly, collect the powder and dry it;

[0055] (2) After drying, the powder was placed in a round alumina crucible and sintered in a muffle furnace at a high temperature, the temperature was raised to 800°C at a rate of 3°C / min and maintained for 12 hours, and then cooled to room temperature to obtain the positive electrode material Na 0.67 Ni 0.15 Li 0.1 Mn 0.55 Ti 0.2 O2;

[0056] (3) The cooled positive electrode material is placed in a mortar and ground for a period of time. After it is completely powdered, it is sealed in an ordinary centrifuge tube and stored in an argon glove box for later use.

[0057] The method of assembling 2032 button cells is the same as above, and the cycle performance at 1C current density is measured as follows: Figure 3 As shown, it exhibits a discharge specific capacity of 90.0 mAh / g. After 100 cycles, a discharge specific capacity of 89.6 mAh / g is obtained, and the capacity retention rate is 99.5%.

[0058] Example 5

[0059] A nickel-manganese-based sodium ion battery positive electrode material Na in Example 5 of the present invention 0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 O2, which comprises the following preparation steps:

[0060] (1) Zn / Ti co-substituted Na 0.67 Ni 0.25-x Zn x Mn 0.75-y Ti y O2 electrode material, where x = 0.05, y = 0.2; with a total mass of about 2g, according to Na 0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 The stoichiometric amount shown in O2 is to mix sodium carbonate, nickel acetate, zinc acetate, manganese carbonate and titanium dioxide, and after mixing evenly, collect the powder and dry it;

[0061] (2) After drying, the powder was placed in a round alumina crucible and sintered in a muffle furnace at a high temperature, the temperature was raised to 800°C at a rate of 3°C / min and maintained for 12 hours, and then cooled to room temperature to obtain the positive electrode material Na 0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 O 2, , its SEM picture is as follows Figure 4 As shown in Figure 2, the particle size is concentrated in the micron or submicron range, which is beneficial to increase the contact area with the electrolyte; its XRD diagram is shown in Figure 2 Figure 5 As shown, in the entire 2θ angle range, it exhibits the characteristics of the P2 structure, and no obvious heterogeneous phase generation is observed, indicating that zinc / titanium is substituted at the corresponding transition metal sites;

[0062] (3) The cooled positive electrode material is placed in a mortar and ground for a period of time. After it is completely powdered, it is sealed in an ordinary centrifuge tube and stored in an argon glove box for later use.

[0063] To verify Na0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 The electrochemical performance of O2. The rate performance of the assembled 2032 button cell is as follows Figure 6 As shown, the current density ranges from 0.2C, 0.5C, 1C, 2C, and 5C, showing 122.9, 108.5, 99.6, 92.0, and 79.1 mAh g, respectively. -1 When the current density of the test returns to 0.2C, Na 0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 The current density of O2 was restored to 118.4 mAh g -1 , proving its excellent rate performance; its cycle performance is as follows Figure 7 As shown, during the first cycle, Na 0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 O2 exhibits approximately 100.0 mAh g -1 The discharge specific capacity shows a capacity retention rate of 79.3% after 200 cycles.

[0064] To verify Na 0.67 Ni 0.2 Zn 0.05 Mn 0.55 Ti 0.2 Electrochemical performance of O2 in full battery. Taking 2032 button battery as an example, the preparation process of full battery is similar to that of half battery, and hard carbon is used for negative electrode instead of sodium sheet. In addition, capacity matching process is required before assembling full battery. Its cycle performance is as follows Figure 8 As shown, at a current density of 0.5C, it still exhibits a capacity retention rate of 70.8% after 100 cycles.

[0065] Example 6

[0066] A nickel-manganese-based sodium ion battery positive electrode material Na according to embodiment 6 of the present invention 0.67 Ni 0.1 Zn 0.15 Mn 0.6 Sn 0.15 O2, which comprises the following preparation steps:

[0067] (1) Zn / Sn co-substituted Na 0.67 Ni 0.25-x Zn x Mn 0.75-ySn y O₂ electrode material, where x = 0.15 and y = 0.15; with a total mass of approximately 2 g, according to the stoichiometry shown in Na 0.67 Ni 0.1 Zn 0.15 Mn 0.6 Sn 0.15 O₂, mix sodium carbonate, nickel acetate, zinc acetate, manganese carbonate, and tin oxalate, collect the powder after mixing evenly and dry it;

[0068] (2) After drying, place the powder in a circular alumina crucible and perform high-temperature sintering in a muffle furnace. Heat it to 800 °C at a rate of 3 °C / min and maintain for 8 h, then cool to room temperature to obtain the positive electrode material Na 0.67 Ni 0.1 Zn 0.15 Mn 0.6 Sn 0.15 O₂.

[0069] (3) Grind the cooled positive electrode material in a mortar for a period of time. After it is completely powdered, seal it in a common centrifuge tube and store it in an argon glove box for later use.

[0070] The assembled 2032-type button battery can exhibit a discharge specific capacity of 93 mAh / g at a current density of 1C and reach an efficiency of 90% after 50 stable cycles.

[0071] Therefore, a positive electrode material for a nickel-manganese-based sodium-ion battery according to the present invention, the positive electrode material is a P2-type layered oxide material, and its chemical general formula is Na 0.67 Ni 0.25-x M1 x Mn 0.75-y M2 y O₂, where M1 is one or more of Zn, Li, or Cu, M2 is one or more of Ti or Sn, 0.05 < x ≤ 0.2, 0.05 < y ≤ 0.2, zinc ions, lithium ions, or copper ions replace part of the nickel ions, and titanium ions or tin ions replace part of the manganese ions. It has the characteristics of accurate structure, excellent performance, low-cost synthesis, environmental protection, and energy conservation, and is suitable for use as a positive electrode material in sodium-ion batteries.

[0072] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific embodiments described. Obviously, many modifications and changes can be made according to the content of this specification. These embodiments are selected and specifically described in this specification to better explain the principle and practical application of the present invention, so that those skilled in the art can understand and utilize the present invention well. The present invention is only limited by the claims and their full scope and equivalents.

Claims

1. A nickel-manganese-based sodium ion battery positive electrode material, characterized in that: The positive electrode material described is a P2-type layered oxide material with a chemical general formula of Na 0.67 Ni 0.25-x M1 x Mn 0.75-y M2 y O2, where M1 is one or more of Zn, Li, or Cu, M2 is one or more of Ti or Sn, 0.05 < x ≤ 0.2, 0.05 < y ≤ 0.2, and zinc ions, lithium ions, and copper ions replace part of the nickel ions, while titanium ions and tin ions replace part of the manganese ions.

2. A method for preparing a positive electrode material as claimed in claim 1, characterized in that: The following steps are involved: (1) according to the stoichiometric ratio of the chemical formula, a sodium salt in an amount of 1 to 1.05 times the stoichiometric amount of the required sodium element is mixed with the remaining metal salts in the required amount; (2) After drying, sintering at 500-800° C. for 6-18 hours, and cooling to room temperature to obtain the positive electrode material.

3. The method for preparing the positive electrode material according to claim 1, characterized in that: The sodium salt described in step (1) is carbonate or acetate, and the remaining metal salts described are one or two of oxides, oxalates, carbonates or acetates.

4. The method for preparing the positive electrode material according to claim 1, characterized in that: Step (2) includes placing the dried metal salt in a muffle furnace and heating it to a set temperature at a rate of 3-5°C / min for sintering.

5. The method for preparing the positive electrode material according to claim 1, characterized in that: Before preparing the positive electrode material, the feasibility thereof is verified: 0.67 Ni 0.25 Mn 0.75 Take sodium salt, nickel salt and manganese salt and mix them evenly. Collect the powder after mixing and dry it. Transfer it to a muffle furnace and sinter it at 500-800℃ for 6-18h to obtain Na 0.67 Ni 0.25 Mn 0.75 O2 material.

6. The method for preparing the positive electrode material according to claim 1, characterized in that: The method also includes grinding the cooled positive electrode material into powder in a mortar, transferring the powder into a centrifuge tube, sealing the tube, and storing the tube in an argon glove box for later use.

7. A sodium ion battery positive electrode plate, characterized in that: The positive electrode sheet comprises the positive electrode material as claimed in claim 1.

8. A sodium ion secondary battery comprising the positive electrode sheet as claimed in claim 7.

Citation Information

Patent Citations

  • Anion valence-varying layer oxide material, and preparation method and application thereof

    CN109560258A

  • P2 type layered metal oxide sodium ion battery positive electrode material and preparation method thereof

    CN115394988A

  • Double-doping-site doped P2 type layered oxide composite material as well as preparation method and application thereof

    CN116845229A

  • Nickel-manganese-based layered oxide positive electrode material for sodium ion battery and preparation method of nickel-manganese-based layered oxide positive electrode material

    CN117117197A

  • Sodium-ion battery positive electrode material with low internal resistance and preparation method of sodium-ion battery positive electrode material

    CN117832441A